Multi-Period Combinatorial Auction Mechanism for Distributed Resource Allocation and Scheduling - LAU, Hoong Chuin (Institutional Knowledge at Singapore Management University, 2007)
We consider the problem of resource allocation and scheduling where information and decisions are decentralized, and our goal is to propose a market mechanism that allows resources from a central resource pool to be allocated to distributed decision makers (agents) that seek to optimize their respective scheduling goals. We propose a generic combinatorial auction mechanism that allows agents to competitively bid for the resources needed in a multi-period setting, regardless of the respective scheduling problem faced by the agent, and show how agents can design optimal bidding strategies to respond to price adjustment strategies from the auctioneer. We apply our approach to handle real-time large-scale dynamic resource coordination in a mega-scale container terminal.